Design Information Consentpasiment Competition Of Desktop Based Dental Poly Information System In Palkesmas Talagabodas Bandung - Yudhi Yanuar; Lilis Emalia; Novia Surya Ghani (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2019)
The research aims to know the design of system information completeness of charging the informed consent of the patient's Poly. teeth to use microsoft Visual Studio 2010 in UPT Puskemas Talagabodas the city of Bandung. The research method used is the method of qualitative techniques of collecting data field studies, interviews, the library and browsing the internet. Methods of use is a waterfall. From a study found no problems, namely : The process of completwness analysis of charging the informed consent is still not running, The informed consent in Poly. teeth are not filled with complete, the lack of socialization of the creation and filling the informed consent, especially in Poly. teeth. The advice is give, namely : start to do the analysis of the completeness of charging the informed consent in accordance with SOP, the medical records that there can be re-socialization back about the creation and filling the informed consent to all staff of other medical right to send out the, should the institution has a system information that can rock the performance of staff medical records more effective in terms of analyzing the completeness of the informed consent and facilitate the creation of the,quipment.